Audience participation in theatre : aesthetics of the invitation - White, Gareth (Palgrave Macmillan, 2013)
"The popularity of participatory work with audiences is greater than ever, but the invitation to participate is rarely given attention as a feature of performance, or an important element of practice in its own right. This book presents a theory of audience participation in the theatre, based on the importance of the moment of invitation and how an event changes character when such an invitation is made. The materials from which theatre performance is made expand to include the audience participant's body and social being, with the participant's prior experience and expectations, and their embodied, affective response to the performance becoming of vital importance. Attending to this expanded set of performance media allows us to begin to articulate the aesthetics of participation, and thereafter to consider the ethics and politics of participation more precisely. "--